BASE PAIRING IN 5-CHLOROURIDINE - Coulter, Charles L. (1969)
5-Chlorouridine has been found to crystallize from water with the molecules of the nucleoside arranged in a base-paired, parallel-stranded ribbon. This type of polymer structure has not been previously considered for nucleic acids. We have constructed a model of polyuridylic acid based upon the 5-chlorouridine crystal structure and wish to suggest it as a plausible molecular complex for this and perhaps other polynucleotides. The crystals are monoclinic, space group P2(1), with a = 7.536 A,b = 5.790 A, c = 13.219 A, and β = 99.89°. There are two 5-chlorouridine molecules per cell. The nucleoside bases are linked across a 2(1) axis with hydrogen bonds between N(3) and O(4). The hydrogen bond length is 2.85 A. The conformation of the base with the ribose about the β-glycosidic bond is anti, with a torsion angle relative to O (1′) of -59.8°. The sugar puckering is C(2′)-endo, and the conformation about the C(4′)—C(5′) bond is gauche-gauche. To build the polymer model, the C(4′)—C(5′) bond was rotated 100° and the sugar-base torsion angle adjusted to -30°. This brought O(3′) and O(5′) of adjacent sugars close enough to make the phosphate ester linkage found in polynucleotides.